Visions of star wars (Nova/Frontline special report., 1986)
This documentary reports on the controversy surrounding the Strategic Defense Initiative Program. Includes excerpts from Presidential news conferences, interviews with military and other experts, and a brief history of the evolution of nuclear weapons.